Implications of socio-economic factors on contraceptive choices among women in North East India: a perspective - Shullai, Wansalan K.; Singh, A. Santa; Sharma, Nalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Socio economic status plays a vital role in determining the awareness and conscious decision making of a woman pertaining to contraceptive use. Family planning has been recognized as one of the most cost-effective solutions for achieving gender equality and equity by empowering women with knowledge and in making reproductive choices by accessing contraceptive methods. Methods: A cross sectional study was conducted on 1000 married women of reproductive age group in the Department of Obstetrics and Gynaecology, NEIGRIHMS, Shillong, Meghalaya, from April 2021 to April 2022. NEIGRIHMS being a tertiary referral centre caters to patients from the entire North Eastern Region of India. A validated questionnaire was used for sociodemographic information, knowledge, awareness and attitude towards different contraceptive methods. Results: Out of 1000 married women, 82.5% women were aware about contraceptive methods, 67.5% women had knowledge on the different types of contraceptive methods available and only 370 (37.04%) of the participants are using at least one type of contraceptive methods and of these, 280 (28%) women preferred condom. Bivariate analysis revealed that factors such as current age, economic status and occupation, were seen to influence the utilization of contraceptive methods among women. Conclusions: While it is noteworthy to see the efforts made by the Government towards achieving the various health targets but sincerer and dedicated efforts are needed to ensure increased awareness about the importance of family planning.